ERF subfamily transcription factors and their function in plant responses to abiotic stresses - Wu, Ying; Li, Xiang; Zhang, Jinnan; Zhao, Haiqing; Tan, Shaolin; Xu, Wanhao; Pan, Jiaqi; Yang, Fan; Pi, Erxu (Frontiers in Plant Science, 2022)
Ethylene Responsive Factor (ERF) subfamily comprise the largest number of proteins in the plant AP2/ERF superfamily, and have been most extensively studied on the biological functions. Members of this subfamily have been proven to regulate plant resistances to various abiotic stresses, such as drought, salinity, chilling and some other adversities. Under these stresses, ERFs are usually activated by mitogen-activated protein kinase induced phosphorylation or escape from ubiquitin-ligase enzymes, and then form complex with nucleic proteins before binding to cis-element in promoter regions of stress responsive genes. In this review, we will discuss the phylogenetic relationships among the ERF subfamily proteins, summarize molecular mechanism how the transcriptional activity of ERFs been regulated and how ERFs of different subgroup regulate the transcription of stress responsive genes, such as high-affinity K+ transporter gene PalHKT1;2, reactive oxygen species related genes LcLTP, LcPrx, and LcRP, flavonoids synthesis related genes FtF3H and LhMYBSPLATTER, etc. Though increasing researches demonstrate that ERFs are involved in various abiotic stresses, very few interact proteins and target genes of them have been comprehensively annotated. Hence, future research prospects are described on the mechanisms how stress signals been transited to ERFs and how ERFs regulate the transcriptional expression of stress responsive genes.